Association Between Serum Uric Acid Levels and Benign Paroxysmal Positional Vertigo: A Systematic Review and Meta-Analysis of Observational Studies - Yang, Xinglong; Yang, Baiyuan; Wu, Mengjun; Wang, Fang; Huang, Xiaodong; Li, Kelu; Mao, Zhiwei; Xu, Zhong; Ren, Hui (Frontiers in Neurology, 2019)
Objective: The objective of the present study was to meta-analyze relevant literature to gain a comprehensive understanding of the potential relationship between serum uric acid levels and risk of benign paroxysmal positional vertigo (BPPV). Methods: The databases of PubMed, Web of Science, Embase, Chinese National Knowledge Infrastructure, Wanfang, and SinoMed were systematically searched for observational case-control studies of the association between BPPV and serum uric acid levels published up to October 2018. Data from eligible studies were meta-analyzed using Stata 12.0. Results: A total of 12 studies were included in the analysis. There was a strong tendency for serum uric acid levels to be associated with risk of BPPV among studies conducted in China (OR 0.69, 95%CI -0.01 to 1.40, p = 0.053), but not among studies outside China (OR 1.07, 95%CI -1.08 to 3.22, p = 0.33). Across all studies, serum uric acid level was significantly higher among individuals with BPPV than among controls (OR 0.78, 95%CI 0.15 to 1.41, p = 0.015), yet it did not independently predict risk of the disorder (OR 1.003, 95%CI 0.995 to 1.012, p = 0.471). Conclusion: The available evidence suggests that BPPV is associated with elevated levels of serum uric acid, but these levels may not be an independent risk factor of BPPV.